2019
DOI: 10.1108/itp-05-2017-0148
|View full text |Cite
|
Sign up to set email alerts
|

Digital innovation in context

Abstract: Purpose The purpose of this paper is to investigate how digital innovation processes emerge and evolve in organizational settings, and how serendipitous and unbounded digital innovations affect organizations’ overall digital directions. Design/methodology/approach The authors draw on an interpretive case study of the Church of Sweden, tracing in detail the design, deployment and governance of an interactive website for digital prayer, the Prayer Web (PW). Findings The findings show how the site came about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 55 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…The implementation of management system can play the functions of planning, organization, leadership, control, etc. to coordinate organizational resources and improve overall performance and the process of implementation and effectiveness of management system, that is, the process of coordinating and planning the various elements of the enterprise and their interrelationships [13]. Supposing P = ½R 1 ðAÞ, R 2 ðAÞ ⋯ R M ðAÞ E is the operation of various resource elements of the enterprise, A represents time, and B X represents the many ways in which the management system coordinates and integrates various resources of the enterprise.…”
Section: Enterprise Management Systemmentioning
confidence: 99%
“…The implementation of management system can play the functions of planning, organization, leadership, control, etc. to coordinate organizational resources and improve overall performance and the process of implementation and effectiveness of management system, that is, the process of coordinating and planning the various elements of the enterprise and their interrelationships [13]. Supposing P = ½R 1 ðAÞ, R 2 ðAÞ ⋯ R M ðAÞ E is the operation of various resource elements of the enterprise, A represents time, and B X represents the many ways in which the management system coordinates and integrates various resources of the enterprise.…”
Section: Enterprise Management Systemmentioning
confidence: 99%
“…Verganti (2009) argues that design is a vehicle to create new meanings by understanding complex and latent human behaviors and synthesizing new design features beyond technology-driven innovation. With this notion, IS and innovation studies have also considered a variety of design features of digital innovation in transforming traditional work styles, organizational behaviors and interaction protocols with new services (Nambisan et al , 2017; Nylén and Holmström, 2019; Yoo et al , 2010). Nevertheless, “contactless service design” has been developed mostly by a technology-driven approach, releasing a research dilemma – how/what contactless service design features could represent the contextual inquiry of human behaviors (desires, needs and requirements) and transform organizational issues and challenges over time?…”
Section: Contactless Socio-technical Transformationsmentioning
confidence: 99%
“…, 2021) as they are more technology-driven with a need for technical and IT related expertise within marketing (Kalaignanam et al. , 2021; Nylén and Holmström, 2019). This includes the emergence of new roles and experts at various levels of marketing (Dwivedi et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, scholars have highlighted that dealing with more endowed consumers (Granados and Gupta, 2013) and handling associated big data require new approaches in marketing (Brinker, 2016;Kalaignanam et al, 2021) and new forms of training, skills and knowledge (Cetindamar Kozanoglu and Abedin, 2021;Herhausen et al, 2020;Kalaignanam et al, 2021). In addition, the emerging changes are not only limited to marketing skills, but, it is suggested that marketing departments are becoming closer to IT (Roy et al, 2021) as they are more technology-driven with a need for technical and IT related expertise within marketing (Kalaignanam et al, 2021;Nyl en and Holmstr€ om, 2019). This includes the emergence of new roles and experts at various levels of marketing (Dwivedi et al, 2021;Di Gregorio et al, 2019) and permeating across the organisation of marketing practices (Gupta et al, 2020;Kalaignanam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%